Экспериментальное исследование истечения водорода высокого давления в пространство с препятствиями после разрыва оболочки - Ignatenko, Д.; Mironov, В.; Penyaz'kov, О.; Skilond', А. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
The experimental setup for the simulation of rupture process of the hydrogen pipelines or chambers with pressure up to 13 MPa has been described. The dependences of the intensity of the shock wave formed by outflowing hydrogen and temperature behind the shock waves from the distance to the rupture place. The interaction of the hydrogen jet with obstacles of different configurations is investigated. The possibility of autoignition and deflagration explosion when high-pressure hydrogen outflows in space with a system of focusing and turbulating obstacles has been experimentally proved . The distributions of the visible flame velocity on the radius of the hearth, the maximum values are exceeding 110 m/sec. The factors contributing to the explosive development of the combustion process and its stages are determined.